PENGUATAN STRATEGI PEMBELAJARAN MENDALAM BERBASIS PENGANTAR AI NOTEBOOKLM UNTUK MENINGKATKAN KUALITAS DAN KOMPETENSI GURU - I Putu Eka Indrawan; Ni Nyoman Parmithi; Ni Luh Putu Yesy Anggreni (Sewagati, 2026)
This community service program aimed to strengthen deep learning-based instructional strategies through the integration of artificial intelligence using NotebookLM to enhance teachers’ quality and competencies at SD 11 Sesetan Denpasar. The program was initiated in response to the dominance of surface learning approaches and limited integration of technology in classroom practices. The method employed a training-based intervention through an interactive workshop involving 25 teachers, consisting of stages of needs analysis, program design, implementation, and evaluation. Data were collected using pre-test and post-test instruments, questionnaires, and participatory observation to assess the effectiveness of the program. The results revealed a significant improvement in teachers’ competencies, with the average score increasing from 65.2 to 88.0 and an N-Gain value of 0.66, categorized as moderate to high effectiveness. In addition, there was a substantial shift in competency levels from low to high and very high categories. Teachers’ responses toward AI integration were highly positive, with an average score of 4.6. These findings indicate that integrating deep learning approaches with AI technology not only improves conceptual understanding but also enhances practical teaching skills. Overall, this program contributes to advancing innovative, adaptive, and meaningful learning practices aligned with 21st-century educational demands.